Koukounaries I : Mycenaean pottery from selected contexts - Koehl, Robert B., (Archaeopress Archaeology, 2021)
The excavations on the Koukounaries Hill, Paros, Greece, conducted under the direction of Demetrius U. Schilardi for the Archaeological Society at Athens from 1976 to 1992, revealed a 12th century B.C.E. Mycenaean building, an Iron Age settlement, and an Archaic sanctuary. This book presents the pottery from five areas inside the building: three large storerooms, the main east-west corridor, and a small shrine, as well as the pottery from a limited reoccupation after the building's fire destruction and abandonment.